A new species of hermit crab of the genus Pagurus Fabricius, 1775 (Crustacea: Anomura: Paguridae) from the southern Caribbean off Venezuela - Lima, Daniel José Marcondes; Lemaitre, Rafael (Zootaxa, 2016)
A male specimen of a new species of the heterogeneous genus Pagurus Fabricius, 1775, collected in 1968 off the Caribbean coast of Venezuela, was discovered among the vast crustacean collections of the Smithsonian Institution. This new species herein described and illustrated is named P. scopaopsis, and is characterized primarily by the presence of: a brush-like setation pattern on the dactyl of the left third pereopod, dense small tubercles on the dorsal surfaces of the dactyl and fixed finger of the right chela, and a raised longitudinal ridge armed with spines on the palm and fixed finger of the left chela.